2005
DOI: 10.1021/es0501971
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Biotic Ligand Model and a Regression Model Predicting Acute Copper Toxicity to the Earthworm Aporrectodea caliginosa

Abstract: The purpose of this study was to develop a terrestrial biotic ligand model (BLM) for predicting acute copper toxicity to the earthworm Aporrectodea caliginosa. To overcome the basic problems hampering development of BLMs for terrestrial organisms, an artificial flow-through exposure system was developed consisting of an inert quartz sand matrix and a nutrient solution, of which the composition was univariately modified. A. caliginosa was exposed for 7 days under varying concentrations of copper and the major c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
82
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 23 publications
3
82
1
Order By: Relevance
“…Protective effects 415 of Mg 2+ and Ca 2+ against Cu toxicity have been previously observed, for example by 416 Kinraide et al (2004) and Luo et al (2008) for root elongation of wheat (Triticum 417 aestivum) in nutrient solutions. On the other hand, Steenbergen et al (2005) found 418 that Mg 2+ and Ca 2+ did not protect the earthworm A. caliginosa against the acute 419 toxicity of Cu 2+ but appeared to contribute to the toxicity. They suggested that co-420 variance between H + , Mg 2+ and Ca 2+ activities was at least partly responsible for these 421 observations.…”
Section: Investigation 393mentioning
confidence: 98%
See 1 more Smart Citation
“…Protective effects 415 of Mg 2+ and Ca 2+ against Cu toxicity have been previously observed, for example by 416 Kinraide et al (2004) and Luo et al (2008) for root elongation of wheat (Triticum 417 aestivum) in nutrient solutions. On the other hand, Steenbergen et al (2005) found 418 that Mg 2+ and Ca 2+ did not protect the earthworm A. caliginosa against the acute 419 toxicity of Cu 2+ but appeared to contribute to the toxicity. They suggested that co-420 variance between H + , Mg 2+ and Ca 2+ activities was at least partly responsible for these 421 observations.…”
Section: Investigation 393mentioning
confidence: 98%
“…The BLM was originally 64 developed to describe the acute toxic effects of metal accumulation at the gill of fish, 65 but has been applied to toxicity data for a number of other aquatic organisms. Some 66 progress has been made in applying the principles of the BLM to soil-dwelling 67 organisms: acute BLMs have been developed for soil organisms such as the 68 earthworm Aporrectodea caliginosa (Steenbergen et al, 2005) …”
mentioning
confidence: 99%
“…Earthworms are of particular use in monitoring the potential exposure of single or multiple soil 30 contaminants as they maintain constant contact with both the solid and liquid phase of soil. In this way, earthworms can be used in partitioning and chemical speciation models to assess bioavailability [2][3][4][5] and the basis for toxic effects 6,7 .…”
mentioning
confidence: 99%
“…For plants, toxicity to particularly wheat (Triticum aestivum), pea (Pisum sativum), and barley (Hordeum vulgare) has been reported using different test solutions and different metal salts [4,[9][10][11]. The use of aqueous solutions has also been reported for different earthworm species [3,12,13]. Few studies have been performed on other soil organisms (M.M.…”
Section: Introductionmentioning
confidence: 99%